Proses Pengeringan Benih Semangka Non-Biji Dengan Memanfaatkan Panas Tray Dryer - Siswoyo Soekarno; Indarto Indarto; Amal Bahariawan; Agus Dharmawan; Achmad Ivo Joan Pamungkas; Nova Sulung Arjasari (Fakultas Teknologi Pangan & Agroindustri (Fatepa) Universitas Mataram dan Perhimpunan Teknik Pertanian (PERTETA), 2024)
The study aimed to design and assess the heat flow capability of a tray dryer to support the process of supplying seedless watermelon seeds. Researchers collaborated with farmers in Seputih Mayang Village, Jember, who partnered with seeds producer of PT East West Seed Indonesia. Drying with a tray dryer that is composed of a frame, plywood walls, heating source, air exhaust cavity, shelves, thermostat, blower, and digital temperature measuring device; heat circulation moves in a zigzag manner. Determination of heat in drying by measuring temperature changes on each shelf. Shelf 1 (bottom) received the most significant heat than the upper shelves. To reduce the moisture content by 12%, the drying machine consumes 2.272 kWh of energy or equivalent to 8179.5 kJ, while the heat released during drying is 1603.800 kJ. Thus, the efficiency of the drying machine is 19.59%.